Survival, Short-Term, and Long-Term Morbidities of Neonates with Birth Weight < 500 g - Bashir, Rani A.; Thomas, Julianne Petrie; MacKay, Margot; Agnew, Jennifer; Hubber-Richard, Philippa; Grunau, Ruth E.; Synnes, Anne (American Journal of Perinatology, 2017)
Objectives The objective of this study was to describe survival, short-term, and long-term morbidities of neonates with birth weight < 500 g.Study Design Retrospective cohort studies to calculate survival, short-term, and long-term morbidity rates of neonates born weighing < 500 g from 1993 to 2012 and neurodevelopmental impairment rates at 4.5 years for births 1993 to 2008 in one center.Results Of 549 inborn neonates with birth weight < 500 g, 4% survived. For live births and neonatal intensive care unit (NICU) admissions, 10 and 55% survived, respectively. Of 28 NICU (inborn and outborn) survivors (median birth weight 460 g and gestation 25.9 weeks [range: 22.6–30.3 weeks]), 71% were inborn, 50% male, and 75% were small for gestational age. One in five neonates was a twin or multiple. Short-term morbidities noted were bronchopulmonary dysplasia (91%), culture proven sepsis (50%), retinopathy of prematurity (41%), and severe brain injury (22%); 27% had no long-term impairment, 23% one, 23% two, 18% three, and 9% four impairments in motor, cognitive, vision, and/or hearing domains. At 4.5 years, 29% had visual impairment, 10% wore hearing aids, 50% had IQ < 70, 18% cerebral palsy, and 68% had low motor scores.Conclusion Only 4% of births < 500 g survived. All survivors had short-term morbidities; 27% neonates survived without long-term major impairments.
Keywords: extremely low birth weight; neurodevelopmental outcome; survival; neonate